1990
DOI: 10.1002/bms.1200190303
|View full text |Cite
|
Sign up to set email alerts
|

Selective sensitivity of highly chlorinated species in negative ion mass spectrometry: Implications for complex mixture analysis

Abstract: In attempts to quantify complex chlorinated hydrocarbon mixtures by negative ion mass spectrometry (MIMS), a selective sensitivity was observed which was not observed using the technique of electron capture detection (ECD) with conventional gas-liquid chromatography. The phenomenon was systematically studied using chlorinated phenols, chlorinated biphenyl isomers and a mixture of chlorinated bicyclic species. Results indicated that for two aromatic series there is an increase in molar response to both ECD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Also, unlike electron impact mass spectrometry, EC-MS does not produce molar responses of the same magnitude across all levels of chlorination of PCBs. For example, Erhardt-Zabik et al showed that the molar response of an octachlorobiphenyl is over 1000 times higher than a dichlorobiphenyl (63). One way to circumvent this problem is to use internal standards of each level of chlorination.…”
Section: B Polychlorinated Biphenylsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, unlike electron impact mass spectrometry, EC-MS does not produce molar responses of the same magnitude across all levels of chlorination of PCBs. For example, Erhardt-Zabik et al showed that the molar response of an octachlorobiphenyl is over 1000 times higher than a dichlorobiphenyl (63). One way to circumvent this problem is to use internal standards of each level of chlorination.…”
Section: B Polychlorinated Biphenylsmentioning
confidence: 99%
“…For example, Ribick et al observed that the ratio of molar responses of heptachlorinated to octachlorinated toxaphene homologues was nearly three times higher in EI-MS than in EC-MS (103). Erhardt-Zabik et al, using chlordane and nonachlor as model compounds to mimic toxaphene components, reported that, although nonachlor possessed only one chlorine more than chlordane, the difference in molar response was about one order of magnitude (63). This observation may affect the analysis of toxaphene in "weathered" samples.…”
Section: G Toxaphenementioning
confidence: 99%
“…Clearly a tremendous difference in sensitivity is observed between the two ionization modes. While in EI signal abundance of CB 126 (S/N 4: 1) is close to the detection limits (S/N 3:1) and CB 169 cannot be differentiated from the noise level the corresponding CI intensities show calculated S/N ratios of over 100 due to the CI effect which becomes more pronounced with an increased degree of chlorination of the molecules similar to electron capture detection (ECD) [15]. This observation is very important as CB 126 and 169 are frequently 5 to 100 times lower in concentration compared to CB 77 in the different extracts.…”
Section: Sensitivity Of Ei-ms and Nci-ms For Coplanar Pcbmentioning
confidence: 96%
“…Unfortunately ECD does not allow an identification while the sensitivity of EI-MS-SIM is lower than that of ECD [12][13][14]. There are a few publications using NCI-MS for the determination of coplanar PCB in biological matrices [15][16][17][18][19]. Recently it has been shown that NCI-MS is a selective and sensitive detection method for the determination of ortho-PCB in sewage sludge providing also structural information [20].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the for-2,5,6-trichloro-PCBs mation of hydrogen inclusion-type fragment ions occurs via dissociative electron capture of (M ] 2H) created by hydrogenation of the non-ionized analyte on the walls of the ion source, a process which appears to be facilitated by some form of heterogeneous catalysis. 2,7,25 The minimal e †ect of the change in ion source temperature on the abundance of hydrogen inclusion-type fragment ions as compared with may be dependent [M [ CH 3 ]õ n the rate of ion formation, which is limited by the di †usion of the analyte to the ion source MeSO 2 -PCB wall and/or the subsequent heterogenous catalysis on the ion source wall, rather than dissociative processes. Table 1 for the individual congeners in each set.…”
Section: Ecni Mass Spectra Of Meso 2 -Pcbsmentioning
confidence: 99%